2024
DOI: 10.1097/j.pain.0000000000003144
|View full text |Cite
|
Sign up to set email alerts
|

Healthy women show more experimentally induced central sensitization compared with men

Alexandros Guekos,
Janis Saxer,
Diego Salinas Gallegos
et al.

Abstract: Women more often experience chronic pain conditions than men. Central sensitization (CS) is one key mechanism in chronic pain that can differ between the sexes. It is unknown whether CS processes are already more pronounced in healthy women than in men. In 66 subjects (33 women), a thermal CS induction protocol was applied to the dorsum of one foot and a sham protocol to the other. Spatial extent [cm2] of secondary mechanical hyperalgesia (SMH) and dynamic mechanical allodynia were assessed as subjective CS pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Unexpectedly, it was found that biological females were less likely than biological males to be seropositive for either RF or ACPAs (adjusted for age, smoking status, body mass index (BMI), and clinical severity scores). Further work is needed to understand whether this is due to unestablished inflammatory pathways in seronegative RA that are chromosomally linked or whether nociceptive pathways, which may differ between men and women [24], lead to a higher proportion of biological females having tender joints and a subsequent diagnosis of RA.…”
Section: Epidemiology Genetics and Clinical Phenotypes: Similarities ...mentioning
confidence: 99%
“…Unexpectedly, it was found that biological females were less likely than biological males to be seropositive for either RF or ACPAs (adjusted for age, smoking status, body mass index (BMI), and clinical severity scores). Further work is needed to understand whether this is due to unestablished inflammatory pathways in seronegative RA that are chromosomally linked or whether nociceptive pathways, which may differ between men and women [24], lead to a higher proportion of biological females having tender joints and a subsequent diagnosis of RA.…”
Section: Epidemiology Genetics and Clinical Phenotypes: Similarities ...mentioning
confidence: 99%